Auxin-Cytokinin Balance Shapes Maize Root Architecture by Controlling Primary Root Elongation and Lateral Root Development - Rivas, M. Ángeles; Friero, Iván; Alarcón, M. Victoria; Salguero, Julio (Frontiers in Plant Science, 2022)
Root system is the responsible for water and nutrients uptake from the soil and therefore its extension is basic for an efficient acquisition. Maize root system is formed by different types of roots and lateral root branching substantially increases the surface for nutrient uptake. Therefore, the regulation of lateral root formation is fundamental in the development of root functions. Root architecture is basically controlled by auxin and cytokinins, which antagonize in the formation of lateral roots (LR) along the primary root axis, with auxin a stimulator and cytokinins inhibitors of LR development. This interaction has been analysed in several zones along the primary root where LRs in different developmental stages were located. The root has been divided in several zones, meristem, elongation zone and mature zone, according to the developmental processes occurring in each one. As Arabidopsis root elongated more slowly than maize root these zones are shorter and its delimitacion is more difficult. However, these zones have previously been delimitated clearly in maize and therefore allow to analyse the effect of exogenous hormones in the several LR developmental stages. The inhibitory effect of cytokinin on lateral root formation was observed in already elongated primary root zones in which initial events to form new lateral roots are taking place. Contrarily, auxin increased LR formation in primary root segments elongated in the presence of the hormone. The inhibitory effect of cytokinin was reversed by auxin in a concentration-dependent manner when both hormones were combined. However, auxin is not able to recover LR development in primary root zones that have been previously elongated only in presence of cytokinin. This antagonistic auxin-cytokinin effect on LR development depended on the balance between both hormones, which controls the root system architecture and determines the formation of LR during the process of initiation.